GAMBARAN PROKRASTINASI AKADEMIK SISWA SMA NEGERI 1 BATUJAJAR PADA MASA PANDEMI COVID-19 - Warnisa, N. Ica; Rosita, Tita (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Academic procrastination is one of the problems that often occurs among high school (SMA) students. This study aims to see the description of the academic procrastination behavior of SMAN 1 Batujajar students. The design of this study used a quantitative descriptive method. The population in this study were students of class XI SMAN 1 Batujajar. Respondents in this study were 107 students of class XI. The technique of taking the subject used a simple random sampling system. The data analysis carried out is the level of categorization of academic procrastination behavior. In this study, it was revealed that the level of academic procrastination behavior of class XI students of SMAN 1 Batujajar generally was in the moderate category when presented, namely 49%, while in the high category 34%, and 17% of students in the low category. Based on the results of the analysis, the launch of the Lay procrastination scale to 107 subjects in terms of gender obtained the following results: (1) 37% of the subjects with 40 students were male; (2) as many as 63% of other subjects with a total of 67 female students. So it can be said that the problem of academic procrastination is still experienced by class XI students at SMAN 1 Batujajar and needs to be handled.